Measuring fusion excitation functions with RIBs using the stacked target technique: Problems and possible solutions - Fisichella M.; Shotter A. C.; Di Pietro A.; Figuera P.; Lattuada M.; Marchetta C.; Privitera V.; Romano L.; Ruiz C.; Zadro M. (EPJ Web of Conferences, 2016)
For measuring fusion excitation functions, the activation technique with a stack of targets offers the considerable advantage that several reaction energies may be simultaneously measured by using one beam energy. However, its main drawback is the degradation of the beam quality as it passes through the stack due to statistical nature of energy loss processes and any non-uniformity of the stacked targets. If not taken properly into account, this degradation can lead to a wrong determination of the fusion excitation function. In this contribution some results of the investigation of this problem are reported.